Development LKPD Based on Open-Ended in Improving Critical Thinking Skills - Miftahul Arifin; Haninda Bharata; Undang Rosidin (International Journal of Trends in Mathematics Education Research, 2020)
This research and development aims to develop LKPD based on open-ended and test its effectiveness on critical thinking skills in mathematics. This development phase begins with research and information gathering, planning, initial product form development, initial field testing, major product revisions, and main field testing. The subjects of this study were the eighth grade students of Al-Huda Jati Agung Junior High School in the academic year 2019/2020. The effectiveness test was conducted to determine the effectiveness of LKPD on the ability to think critically mathematically. The LKPD based on the open-ended developed was suitable for use in the excellent category based on the results of the validation of two expert validators. Preliminary field trial results indicate that LKPD is included in the good category. Field test results show that the average increase in students 'critical thinking skills in mathematics using LKPD on an open-ended basis is higher than the increase in average students' critical thinking skills in mathematics that do not use LKPD based on open-ended, so it can be concluded that LKPD based on open-ended effective for improving students' critical thinking math skills.